2020
DOI: 10.1097/md.0000000000019735
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic joint infection due to Candida species

Abstract: Introduction: The increase in the number of patients with prosthetic joints will entail a rise in the absolute number of infections associated with these procedures. Although less frequent, infections by Candida species are also expected to increase, and the clinical and surgical management of these cases is based on case reports and opinion of specialists. The objective of the present study was to review the available literature and describe the cases of prosthetic joint infection caused by Candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…As people pay more attention to the PJI, the infection rate following arthroplasty is decreasing. However, the increase in the number of patients with prosthetic joints in recent decades has added to the absolute number of PJI cases [ 3 , 4 ]. Recently, a review showed that, with more arthroplasty cases, the cost of revision surgery for infection has put greater pressure on healthcare budgets [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As people pay more attention to the PJI, the infection rate following arthroplasty is decreasing. However, the increase in the number of patients with prosthetic joints in recent decades has added to the absolute number of PJI cases [ 3 , 4 ]. Recently, a review showed that, with more arthroplasty cases, the cost of revision surgery for infection has put greater pressure on healthcare budgets [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other species, such as C. glabrata and C. tropicalis, were more anecdotic (3–7% and 2–4%, respectively). Smaller series have found similar results [ 13 , 14 ], and in a recent review of the literature, C. albicans (47.3%) was the most frequent strain isolated, followed by C. parapsilosis (22.3%) [ 15 ], but epidemiology may still vary among regions.…”
Section: Epidemiologymentioning
confidence: 76%
“…(3) Immunosuppression secondary to malignant diseases, immunodeficiencies, or immunosuppressive therapy. Other risk factors reported in patients with CPJIs have been older age [ 18 ], diabetes, rheumatoid arthritis, malnutrition, and tuberculosis, which probably also reflect alterations in host immunity [ 2 , 12 , 13 , 14 , 23 ]. Other series have also identified that multiple previous surgeries at the site of the CPJI are also a risk factor [ 2 , 13 , 23 , 24 ].…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations